Web-Based Integrated Information System Monitoring Data Reports on the Implementation of the DKI Jakarta COVID-19 Vaccination - Lumbantoruan, Rutman (Fundamental Management Journal, 2021)
CoronaVirus or COVID-19 is a disease that spreads so quickly that it causes people who are infected to get sick and even die. The cause of the rapid spread of this virus is because of the way it is transmitted from one person infected with this virus to others in the vicinity through the air. Given these conditions, the researchers analyzed the design of information technology systems, especially the online system for registration of COVID-19 vaccinations, such as registration of the day of implementation, date of implementation, selection of locations and types of vaccines, and vaccination capacitation, especially in the DKI Jakarta area. People who come to the location of the COVID-19 vaccination, such as health centers, hospitals and other locations that have been determined. This information technology has been developed and has been implemented to help the community, especially the DKI Jakarta area, as a means of registering online for the implementation of vaccinations that are available and listed in a web-based information system. In this study, the first thing to do is to analyze the design of the information system using the Prototype method, which aims to make the system design that is built results in the development of appropriate software, and can help and facilitate the community in carrying out vaccinations, so that the DKI Jakarta government can monitor the implementation before and after vaccination, as well as managing data on people who have or have not received the COVID-19 vaccination as a reference in making decisions and policies of the DKI Jakarta Government. Keywords – COVID-19 Vaccination, DKI Jakarta, Monitoring, Information System, Online Web-base.